2022
DOI: 10.1002/admi.202202077
|View full text |Cite
|
Sign up to set email alerts
|

Thin‐Film Composite Cyclomatrix Poly(Phenoxy)Phosphazenes Membranes for Hot Hydrogen Separation

Abstract: An interfacial polymerization process is introduced for the fabrication of thermally stable cyclomatrix poly(phenoxy)phosphazenes thin‐film composite membranes that can sieve hydrogen from hot gas mixtures. By replacing the conventionally used aqueous phase with dimethyl sulfoxide/potassium hydroxide, a variety of biphenol molecules are deprotonated to aryloxide anions that react with hexachlorocyclotriphosphazene dissolved in cyclohexane to form a thin film of a highly cross‐linked polymer film. The film memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 56 publications
0
16
1
Order By: Relevance
“…This is evidenced by the release of H 2 O, CH 3 S, and Cl (Figure S4). The decrease in weight at temperatures exceeding 300 °C is distinct from the behavior of the diphenol-based materials of our previous study . For those materials, it was shown that the almost complete substitution of the Cl groups on the HCCP by Ar–O groups prevents the HCCP ring from opening at elevated temperatures, and no appreciable weight loss of these materials is observed for temperatures below 400 °C.…”
Section: Resultscontrasting
confidence: 62%
See 4 more Smart Citations
“…This is evidenced by the release of H 2 O, CH 3 S, and Cl (Figure S4). The decrease in weight at temperatures exceeding 300 °C is distinct from the behavior of the diphenol-based materials of our previous study . For those materials, it was shown that the almost complete substitution of the Cl groups on the HCCP by Ar–O groups prevents the HCCP ring from opening at elevated temperatures, and no appreciable weight loss of these materials is observed for temperatures below 400 °C.…”
Section: Resultscontrasting
confidence: 62%
“…The decrease in weight at temperatures exceeding 300 °C is distinct from the behavior of the diphenol-based materials of our previous study. 14 For those materials, it was shown that the almost complete substitution of the Cl groups on the HCCP by Ar−O groups prevents the HCCP ring from opening at elevated temperatures, and no appreciable weight loss of these materials is observed for temperatures below 400 °C. Because the extent of substitution of Cl groups for the AHC-HCCP materials is much lower, the thermally induced opening of HCCP rings is more probable, causing the distinct thermal evolution of the mass.…”
Section: Materials Characterizationmentioning
confidence: 99%
See 3 more Smart Citations